INNV-08. LOW AND INTERMEDIATE GRADE GLIOMA UMBRELLA STUDY OF MOLECULAR GUIDED THERAPIES (LUMOS) STUDY. (12th November 2021) - Kong, Benjamin; Sim, Hao-Wen; Amanuel, Benhur; Day, Bryan; Buckland, Michael; Verhaak, Roel; Yip, Sonia; Johns, Terrance; Lwin, Zarnie; Rosenthal, Mark; Nowak, Anna K; Barnes, Elizabeth H; et al.
Abstract: BACKGROUND: Grade 2 and 3 (G2/3) gliomas are the second largest group of brain tumors in adults. Although the prognosis for G2/3 gliomas at the time of relapse mirror those of glioblastoma, there are few trials in this space. METHODS: LUMOS was a national multi-center pilot study for patients with relapsed G2/3 gliomas designed to match contemporaneous tissue obtained at the time of disease progression with subsequent targeted therapies. The objective was to establish the feasibility of a precision oncology, umbrella approach to obtain and type tissue within a useful timeframe. As a key feature of LUMOS, a multidisciplinary Molecular Tumor Advisory Panel (MTAP) with subspecialty neuro-oncology expertise was formed to interpret the complex genomic information and provide a simplified recommendation to the treating physician. RESULTS: Ten patients (median age 42: range 32-62; four G2 astrocytoma, one G3 astrocytoma, three G2 oligoendroglioma, one G3 oligodendroglioma, one mixed tumor) were enrolled in the study. Eight patients had biopsies within 6 months of study entry whilst two underwent a biopsy during the study. All patients had potentially targetable alterations (10 IDH, 3 FGFR, 2 PIK3K, CCND3, NRAS, CDK4, PRPRZ1-MET fusion and MET amplification). Matched therapies were delivered for two patients via compassionate access outside the study. The median turnaround time (TAT) of MTAP reports was 6.2 weeks (range 4.2-9.7 weeks) but 4.6 weeks when lag time for shipping was removed. CONCLUSION: LUMOS confirmed that this design was feasible with good turnaround times. The MTAP facilitated education and support for treating physicians. Thes findings support moving to a larger study using contemporaneous and longitudinal tissue samples matched with targeted therapies as part of a comprehensive umbrella study design. Delivery and interpretation of molecular data is a challenge shared across oncology which may be mitigated with a neuro-oncology specific molecular tumor board.